2023
DOI: 10.3389/fpls.2023.1069830
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase1: A glucose sensor involved in drought stress response and sugar metabolism depending on its kinase activity in strawberry

Abstract: Hexokinase1 (HXK1) is a bifunctional enzyme that plays indispensable roles in plant growth, nitrogen utilization, and stress resistance. However, information on the HXK family members of strawberries and their functions in glucose sensing and metabolic regulation is scarce. In the present study, four HXKs were firstly identified in the genome of Fragaria vesca and F. pentaphylla. The conserved domains of the HXK1s were confirmed, and a site-directed mutation (S177A) was introduced into the FpHXK1. FpHXK1, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Yang et al ( 58 ) showed that MdFRK2 is the key gene for fructose phosphorylation in apples and the homeostasis and signaling of fructose content can regulate sugar metabolism and content. Transient overexpression of FpHXK1 and its kinase-deficient mutants had different effects on the contents of glucose, sucrose, anthocyanins and total phenols in strawberry fruit ( 59 ). F6P can re-synthesize sucrose under the catalysis of sucrose phosphate synthase (SPS).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al ( 58 ) showed that MdFRK2 is the key gene for fructose phosphorylation in apples and the homeostasis and signaling of fructose content can regulate sugar metabolism and content. Transient overexpression of FpHXK1 and its kinase-deficient mutants had different effects on the contents of glucose, sucrose, anthocyanins and total phenols in strawberry fruit ( 59 ). F6P can re-synthesize sucrose under the catalysis of sucrose phosphate synthase (SPS).…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was found in strawberry ( Fragaria pentaphylla ). Inhibition of FpHXK1 kinase activity weakened the strawberry plant’s responses to drought stress [ 25 ]. Meanwhile, about HXK2, researchers found that Arabidopsis plants transgenic for Glycine max HXK2 ( GmHXK2 ) showed improved tolerance to salt stress [ 24 ].…”
Section: Hexokinasesmentioning
confidence: 99%
“…To ensure further signaling steps, HXK1 requires interaction with other proteins. It was documented, that HXK1 can form the complex with the VHA-B (vacuolar proton pump -subunit B), or components of Polycomb Repressive Complex 2 -SWN (SWINGER), and -CLF (CURLY LEAF) [13]. Interaction of HXK1 with the CLF and SWN leads to the trimethylation of H3 lysine in the promoter region of the target genes and therefore stimulates the expression of target genes [13].…”
Section: Indirect Light Sensingmentioning
confidence: 99%
“…It was documented, that HXK1 can form the complex with the VHA-B (vacuolar proton pump -subunit B), or components of Polycomb Repressive Complex 2 -SWN (SWINGER), and -CLF (CURLY LEAF) [13]. Interaction of HXK1 with the CLF and SWN leads to the trimethylation of H3 lysine in the promoter region of the target genes and therefore stimulates the expression of target genes [13]. In the nucleus of Arabidopsis thaliana, the presence of glucose leads to increased degradation of EIN3 (Ethylene insensitive 3) by AtHXK1, resulting in a diminished response to ethylene-induced signaling [13].…”
Section: Indirect Light Sensingmentioning
confidence: 99%
See 1 more Smart Citation